2017
DOI: 10.1002/ijc.30924
|View full text |Cite
|
Sign up to set email alerts
|

Prostate and breast cancer in four Nordic countries: A comparison of incidence and mortality trends across countries and age groups 1975–2013

Abstract: In recent decades, management of prostate and breast cancer patients has changed considerably. The purpose of our study is to interpret patterns of prostate and breast cancer incidence and mortality in four Nordic countries across age groups and time periods. Prostate and breast cancer incidence and mortality data (1975-2013) were obtained from the NORDCAN database. Joinpoint regression models were used to identify changes in the trends. A more prominent increase in prostate than breast cancer incidence was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 45 publications
5
26
1
1
Order By: Relevance
“…The commercial availability of PSA testing from the middle to late 1980s led to intensive use of the test for early detection and diagnostics, and incidence rates rapidly increased, first in the United States and, within a few years, in greater Europe, notably in several Nordic countries, Australia, and Canada . These trends have been followed by declines as the pool of prevalent cases diminishes; in the United States, the 2012 recommendation against the routine use of PSA testing by the US Preventive Services Task Force may have partly driven trends downward in recent years (although this organization currently recommends that this decision should be an individual one), whereas incidence in the Nordic countries has either declined (Denmark, Finland, and Sweden) or has been stable (Norway) since the middle 2000s . However, rates are on the rise in countries where PSA testing became more widely used later, including the United Kingdom, Japan, Brazil, Costa Rica, and Thailand .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The commercial availability of PSA testing from the middle to late 1980s led to intensive use of the test for early detection and diagnostics, and incidence rates rapidly increased, first in the United States and, within a few years, in greater Europe, notably in several Nordic countries, Australia, and Canada . These trends have been followed by declines as the pool of prevalent cases diminishes; in the United States, the 2012 recommendation against the routine use of PSA testing by the US Preventive Services Task Force may have partly driven trends downward in recent years (although this organization currently recommends that this decision should be an individual one), whereas incidence in the Nordic countries has either declined (Denmark, Finland, and Sweden) or has been stable (Norway) since the middle 2000s . However, rates are on the rise in countries where PSA testing became more widely used later, including the United Kingdom, Japan, Brazil, Costa Rica, and Thailand .…”
Section: Resultsmentioning
confidence: 99%
“…37,38 These trends have been followed by declines as the pool of prevalent cases diminishes; in the United States, the 2012 recommendation against the routine use of PSA testing by the US Preventive Services Task Force may have partly driven trends downward in recent years (although this organization currently recommends that this decision should be an individual one), 39 whereas incidence in the Nordic countries has either declined (Denmark, Finland, and Sweden) or has been stable (Norway) since the middle 2000s. 40 However, rates are on the rise in countries where PSA testing became more widely used later, including the United Kingdom, Japan, Brazil, Costa Rica, and Thailand. 37,38,41 Incidence is also rising in several African populations, including Kampala (Uganda) and in the black population of Harare (Zimbabwe), although, because the registry catchment areas comprise urban populations, it remains difficult to attribute the trends to changes in risk or to enhanced diagnostic capabilities and increased PSA testing.…”
Section: Prostate Cancermentioning
confidence: 99%
“…A survey conducted in the Eastern Mediterranean Region analysed the trends of deaths and DALYs from 2005 to 2015 by different cancers and found that mortality and DALY rates due to breast cancer stabilized over a 10-year period 1 . In Denmark and Finland, a reduction in breast cancer mortality rates over 25 years (1985–1989 to 2009–2013) has been reported 15 , and in the U.S., there was a decline in breast cancer mortality rates from 1990 to 2009 in all ethnic groups 16 . From 1990 to 2015, public health policies were created in Brazil, which resulted in improvements in cancer screening and treatment services, such as the National Oncology Policy 17 .…”
Section: Discussionmentioning
confidence: 98%
“…al. [16] showed that women under 50 years had a more profound drop in mortality than older patients. Notably, we observed a 40% increase in breast cancer diagnoses between 1989 and 2013.…”
Section: Discussionmentioning
confidence: 99%